Food and Drug Administration Approval Summary: Odevixibat (Bylvay) for the Treatment of Pruritus With Progressive Familial Intrahepatic Cholestasis - Sojeong Yi; Insook Kim; Rebecca Hager; Marian M. Strazzeri; Lili Garrard; Toru Matsubayashi; Ruby Mehta (Gastro Hep Advances)
On July 20, 2021, the Food and Drug Administration approved odevixibat (Bylvay) for the treatment of pruritus in patients 3 months of age and older with progressive familial intrahepatic cholestasis (PFIC). PFIC is a rare disease that results in impaired bile secretion and transport, leading to cholestatic liver injury. Odevixibat is a reversible inhibitor of the ileal bile acid transporter. It decreases the reabsorption of bile acids from the terminal ileum (distal small intestines). Approval was based on the improvement in pruritus demonstrated in a 24-week randomized double-blind placebo-controlled trial conducted in 62 pediatric subjects, aged 6 months to 17 years, with a confirmed molecular diagnosis of PFIC type 1 or type 2 with the presence of pruritus at baseline. Given the subjects’ young age, a single-item observer-reported outcome (ObsRO) was used to measure scratching as observed by the caregiver. Subjects had an average scratching score of greater than or equal to 2 (medium scratching) in the 2 weeks before baseline. The mean percentage of ObsRO assessments over the 24-week treatment period that were scored as 0 (no scratching) or 1 (a little scratching) was 35.4% and 30.1% for 40 mcg/kg/day and 120 mcg/kg/day odevixibat treatment, respectively, compared to 13.2% for placebo. There was general alignment between subject and caregiver assessments of worst weekly pruritus severity among subjects for whom both patient-reported outcome (Worst Weekly Itching Score) and ObsRO (Worst Weekly Scratching Score) data were available. The most common adverse reactions included diarrhea, liver test abnormalities, vomiting, abdominal pain, and fat-soluble vitamin deficiency. The benefit-risk assessment for odevixibat for the treatment of pruritus in the labeled population was considered favorable.